Esposizione a latice e impiego di guanti in ambito sanitario: vecchie e nuove problematiche / Latex exposure and gloves’ use in health settings: old and new issues - Crippa, M. (La Medicina del Lavoro, 2008)
Latex exposure and gloves’ use in health settings: old and new issuesThe diffusion of the “universal precautions”, promoted in 1987 by the Center for Disease Control and Prevention, dramatically increased the use of latex glove in health care settings for protection against the HIV and HBV. The increased demand caused an increased production of gloves, a reduction in processing time and a different chemical treatment of rubber trees which lowered the glove quality, that means high levels of antigens and high powder content. This situation caused an increase of frequency of allergic (type I and type IV) and irritant reactions to latex gloves in health care workers. Recommendations and guidelines for the prevention of latex allergy in health care settings were available from 1995 both in Italy and in other countries. When properly applied, the preventive effectiveness of these suggestions has been demonstrated, but unfortunately the guidelines are not widely adopted as we could think and the frequency of latex allergy and sensitization in health care workers is not as reduced as it could be expect. This could be due also to the fact that some practical issues are still open, for example: the possibility of assessing the real glove quality and the reliability of information provided by manufacturers that often are inaccurate and incomplete; the necessity to update the regulations in force to higher quality standards; the availability of procedures for the selection, purchase and use of gloves in relation to specific tasks within health care setting; the involvement of occupational physicians in the management of these procedures; clear indications of limit values for extractable latex allergens in medical and common latex devices; the assessment of the real protective efficacy against chemicals and biological agents of new synthetic rubber gloves. An Italian working group of occupational health professionals, involved for a long time in the management of glove and latex related problems in health care settings, finalized a consensus document with practical suggestions and possibly answers to the above mentioned questions.